2022
DOI: 10.1155/2022/8890434
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mesenchymal Stem Cell-Derived Exosome-Enclosed miR-181a Induces CD4+CD25+FOXP3+ Regulatory T Cells via SIRT1/Acetylation-Mediated FOXP3 Stabilization

Abstract: Bone marrow mesenchymal stem cells (BMSCs) have been identified as a potential therapeutic approach to immune-related diseases. Here, we show that BMSC-derived exosomes promote FOXP3 expression and induce the conversion of CD4+ T cells into CD4+CD25+FOXP3+ Treg cells, which is significant for immunosuppressive activity. We found that miR-181a-5p is upregulated in BMSC-derived exosomes and can be transferred to CD4+ T cells. In CD4+ cells, miR-181a directly targets SIRT1 and suppresses its expression. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition, bone marrow-derived mesenchymal stem cell (BMSC)-derived exosome miR-181a is essential for the maintenance of immune tolerance. It induced CD3+CD1+FOXP3+ Treg cells production via SIRT4/acetylation/FOXP3 ( 158 ). BMSC-derived exosomes can partially transfer miR-17a-6p to suppress IL-23 expression and thereby balance the Th17/Treg ratio in aplastic anemia ( 159 ).…”
Section: Roles Of Exosomal Mirnas In Vitiligomentioning
confidence: 99%
“…In addition, bone marrow-derived mesenchymal stem cell (BMSC)-derived exosome miR-181a is essential for the maintenance of immune tolerance. It induced CD3+CD1+FOXP3+ Treg cells production via SIRT4/acetylation/FOXP3 ( 158 ). BMSC-derived exosomes can partially transfer miR-17a-6p to suppress IL-23 expression and thereby balance the Th17/Treg ratio in aplastic anemia ( 159 ).…”
Section: Roles Of Exosomal Mirnas In Vitiligomentioning
confidence: 99%
“…It has been reported that miRNA-181 is overexpressed in CD138 + PCs from MM patients [ 9 , 77 ]. miR-181 is released to BME by BMSC-derived exosomes and may be uptaken by PCs [ 78 ]. This miRNA epigenetically regulates the tumor-suppressor activity of p53 and Sirtuin 1 (SIRT1) [ 9 , 78 ].…”
Section: Bm Tumor Microenvironment and The Critical Reactions In Mult...mentioning
confidence: 99%
“…miR-181 is released to BME by BMSC-derived exosomes and may be uptaken by PCs [ 78 ]. This miRNA epigenetically regulates the tumor-suppressor activity of p53 and Sirtuin 1 (SIRT1) [ 9 , 78 ]. Sirt1 is a histone deacetylase (HDAC) and plays an important role in epigenomic profiling in MM by modulating the expression of P53 and miRNA-34a, and its targeting is suggested as a treatment strategy for MM [ 31 ].…”
Section: Bm Tumor Microenvironment and The Critical Reactions In Mult...mentioning
confidence: 99%